Implementing OKRs (Objectives and Key Results) in Technical Project Management - Mohan, Priyank (Journal of Quantum Science and Technology, 2024)
Objectives and Key Results (OKRs) are an effective framework used to enhance alignment, focus, and transparency in organizational management. In the context of technical project management, OKRs can significantly improve project execution by fostering collaboration, tracking progress, and measuring outcomes. This manuscript explores the principles and implementation of OKRs in technical project management. It presents a literature review of prior research on OKRs and project management frameworks, details the methodology of integrating OKRs into technical projects, and evaluates the results through case studies. The study concludes with the scope, challenges, and limitations of OKRs, providing insights into the framework’s potential to enhance team performance and project outcomes.